Protecting emergency responders, - Willis, Henry H. (Rand, Science and Technology Policy Institute, 2006)
This monograph serves as a technical source for National Institute for Occupational Safety and Health (NIOSH) incident commander guidelines for emergency response immediately following large structural collapse events. It characterizes response activities and expected hazards, and develops guidelines for selecting appropriate personal protective equipment (PPE). The partial or complete collapse of a multistory building creates an array of physical, chemical, and biological hazards. The most significant uncertainties are the composition and magnitude of the hazards present in the postcollapse environment. Although hazard monitoring can reduce these uncertainties, this type of monitoring will not be available during the first few postcollapse hours. The guidelines focus on three issues that present unique challenges in the response to a multistory-building collapse: (1) protection from biological hazards; (2) protection from inhalation of hazardous materials; and (3) required modifications to responders' typical PPE ensembles because of the duration and intensity of the response. However, selecting and purchasing appropriate PPE does not alone ensure safety; the guidelines also address the need to provide adequate supply of equipment and training so that it is used correctly.